1982
DOI: 10.2337/diab.31.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise (Running) on Serum Glucose, Insulin, Glucagon, and Chromium Excretion

Abstract: Chromium is involved in normal glucose metabolism. To test whether chromium is also associated with the exercise-induced increases in glucose utilization, urinary chromium excretion, serum glucose, insulin, and glucagon of nine male runners (23-46 yr) were evaluated. Blood samples were taken prior to, immediately following, and 2 h after a strenuous 6-mile run. Urine samples were also taken at these times, and total daily urine collections were made the day of the run and the following day. Mean serum glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 0 publications
4
17
1
Order By: Relevance
“…Urinary creatinine has been demonstrated to increase by as much as 50-100 % following a strenuous 6-mile run, 100-km marathon, and 70-90-km cross country ski race [252][253][254]. It is difficult to ascertain whether observed changes in a selected analyte are negatively affected by this change.…”
Section: Creatininementioning
confidence: 94%
See 1 more Smart Citation
“…Urinary creatinine has been demonstrated to increase by as much as 50-100 % following a strenuous 6-mile run, 100-km marathon, and 70-90-km cross country ski race [252][253][254]. It is difficult to ascertain whether observed changes in a selected analyte are negatively affected by this change.…”
Section: Creatininementioning
confidence: 94%
“…Moreover, urine also provides a reliable diagnostic medium for the assessment of hydration through creatinine [254,297] and SG [26] from endurance exercise to body-building resistance training, as well as showing promise as a medium for the detection of exercise- neopterin, NT-proBNP N-terminal prohormone of brain natriuretic peptide, ra receptor antagonist, S100B S100 calcium binding protein B, Sig.…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Another band of intermediate molecular weight also appears (centered at approximately fraction 73); the identity of this band will be the subject of future studies, but it could represent a degradation product of transferrin. Numerous studies have demonstrated that chromium is released in urine within 90 min of a dietary stress such as high sugar intake [6,7,43,44,45,46]. Morris et al [4] have shown that chromium release in response to sugar intake is actually the result of increased blood insulin concentrations (that are produced in response to increasing sugar levels in the blood).…”
Section: Cr Intake By Rat Liver In Vitromentioning
confidence: 99%
“…In the first two years of the onset of diabetes, plasma Cr levels inversely correlated with plasma glucose concentrations, but this trend disappeared for patients with the disease for longer duration. In healthy individuals, increased urinary Cr output and decreased serum Cr levels have been observed in response to increases in serum glucose or insulin [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%